Variation in the Association between Antineoplastic Therapies and Venous Thromboembolism in Patients with Active Cancer - Giustozzi, Michela; Curcio, Antonio; Weijs, Bob; Field, Thalia S.; Sudikas, Saulius; Katholing, Anja; Wallenhorst, Christopher; Weitz, Jeffrey I.; Martinez, Carlos; Cohen, Alexander T. (Thrombosis and Haemostasis, 2020)
Background Venous thromboembolism (VTE) is a major cause of death in cancer patients. Although patients with cancer have numerous risk factors for VTE, the relative contribution of cancer treatments is unclear.Objective The objective of this study is to evaluate the association between cancer therapies and the risk of VTE.Methods From UK Clinical Practice Research Datalink, data on patients with first cancer diagnosis between 2008 and 2016 were extracted along with information on hospitalization, treatments, and cause of death. Primary outcome was active cancer-associated VTE. To establish the independent effects of risk factors, adjusted subhazard ratios (adj-SHR) were calculated using Fine and Gray regression analysis accounting for death as competing risk.Results Among 67,801 patients with a first cancer diagnosis, active cancer-associated VTE occurred in 1,473 (2.2%). During a median observation time of 1.2 years, chemotherapy, surgery, hormonal therapy, radiation therapy, and immunotherapy were given to 71.1, 37.2, 17.2, 17.5, and 1.4% of patients with VTE, respectively. The active cancers associated with the highest risk of VTE—as assessed by incidence rates—included pancreatic cancer, brain cancer, and metastatic cancer. Chemotherapy was associated with an increased risk of VTE (adj-SHR: 3.17, 95% confidence interval [CI]: 2.76–3.65) while immunotherapy with a not significant reduced risk (adj-SHR: 0.67, 95% CI: 0.30–1.52). There was no association between VTE and radiation therapy (adj-SHR: 0.91, 95% CI: 0.65–1.27) and hormonal therapies.Conclusion VTE risk varies with cancer type. Chemotherapy was associated with an increased VTE risk, whereas with radiation and immunotherapy therapy, an association was not confirmed.
Keywords: antineoplastic agents; chemotherapy; immunotherapy; radiotherapy; venous thromboembolism